Characteristics of Behavioral and Psychological Symptoms of Dementia in Patients with Major Neurocognitive Disorder due to Vascular Disease - อภิสิทธิ์ภิญโญ ศิรินภา; รังษีขจี พูนศรี; พหลภาคย์ พงศธร; พหลภาคย์ ภัทรี; พุทธรักษ์ วรินทร (Journal of the Psychiatric Association of Thailand, 2019)
Objective : To study the prevalence and the trend of change during 24 weeks of follow-ups in pattern of behavioral and psychological symptoms of dementia (BPSD), the associated factors among patients with major neurocognitive disorder due to vascular disease. Method : A retrospective chart review of 54 patients with major neurocognitive disorder due to vascular disease who attended psychiatric outpatient department at Srinagarind Hospital during 2014 to 2018 was performed. Demographic data, history of major neurocognitive disorder due to vascular disease and factor associated with BPSD were collected. Neuropsychiatric inventory questionnaire-Thai version (NPI-Q Thai) was used to measure BPSD in these patients. Data analysis used descriptive statistics for baseline characteristic and percentage of BPSD and analysis statistic for factors associated with BPSD using correlation analysis. Results : Among 54 patients with major neurocognitive disorder due to vascular disease, predominately males (29 case, 53.7%), with a mean age of 71.9±8 years, mostly mildly ill (27.8-38.9%) according to clinical global impression scale (CGI-S). The prevalence of BPSD were 87% and 83.3% in the 1st and 24th week, respectively. Most common BPSD was apathy (50-55.6%), the second frequent was irritability (31.5%-38.9%). The least frequent BPSD was elation (3.7-9.3%). There is no statistically significant correlation between various factors and prevalence of BPSD. Conclusion : The prevalence of BPSD in patients with major neurocognitive disorder due to vascular disease was high and a little change during 24 weeks of follow-ups. Patterns of BPSD were the same at both points. None of clinical factors were found to be correlated with BPSD. Early detection and multidisciplinary approach for patients, caregivers and their families should be considered.